BAHASA IBU DALAM TULISAN DESKRIPSI SISWA SMP KELAS VII - Fitriyani, Dwi (JURNAL PESONA, 2016)
Mother tongue is the first language from childern. The mother tongue of State JuniorHigh School Number I Banyumas student dominate with local language such asJavanese of habitual society in communication there. The Childern get difficulties inlanguage learning especially descriptive. The objective of this research knows ofmother toungue used in descriptive text made by Junior High School number IBanyumas. This research is using analysis descriptive that mother tongue as theobject of the research. The data collecting technique is using test and interview. Theresearcher gives a picture to the students then describes the picture. Furthemore, theresearcher is interviewing the students about their identity. The result showed that themost of the students still using their mother tongue, Javanese then their nationallanguage, bahasa Indonesia.Key Words:Mother Tongue, Descriptive Text.